The influence of perception and motivation on the interest of career in the field of taxation students majoring in accounting of the faculty of economics Universitas Negeri jakarta - Indra Pahala; Lisa Rachmawati; Tresno Eka Jaya (Jurnal Ilmiah Wahana Akuntansi, 2017)
This study aimed to determine the effect of perception and motivation to Students Career Interests in Taxation of Departement of Accounting Faculty of Economics at the State University of Jakarta. This study used 75 students S1 Departement of Accounting, State University of Jakarta which is still active academic year 2010. Data used in this study is primary data and selection of samples using a convenience sampling method. The analytical tool used is multiple linear regression analysis at a significance level of 5%. The first phase of testing the validity and reliability of the statement of each variable. The second stage, performing variable regression perception and motivation towards a career in the field of taxation the interest of students. The results of testing the feasibility of the model shows that the two independent variables, namely perception and motivation affect the career interests of students in the field of taxation Accounting Department of Economics at the State University of Jakarta simultaneously.